The Holocaust and North Africa - Boum, Aomar HerausgeberIn; Stein, Sarah Abrevaya HerausgeberIn (Stanford University Press, 2019)
Between metropole and French North Africa : Vichy's anti-Semitic legislation and colonialism's racial hierarchies / Daniel J. Schroeter -- The persecution of the Jews in Libya between 1938 and 1945 : an Italian affair? / Jens Hoppe -- The implementation of anti-Jewish laws in French West Africa : a reflection of Vichy anti-Semitic obsession / Ruth Ginio -- "Other places of confinement" : Bedeau internment camp for Algerian Jewish soldiers / Susan Slyomovics -- Blessing of the bled : rural Moroccan Jewry during World War II / Aomar Boum and Mohammed Hatimi -- À la recherche de Vichy : the Commissariat général aux questions juives and the implementation of the Statut des juifs in Tunisia / Daniel Lee -- Eyewitness Djelfa : daily life in a Saharan Vichy labor camp / Aomar Boum -- The ethics and aesthetics of restraint : Judeo-Tunisian narratives of occupation / Lia Brozgal -- Fissures and fusions : Moroccan Jewish communists and World War II / Alma Heckman -- Re-centering the Holocaust (again) / Omer Bartov -- Paradigms and differences / Susan Rubin Suleiman -- Sephardim and Holocaust historiography / Susan Gilson Miller -- Stages in Jewish historiography and collective memory / Haim Saadoun -- A memory that is not one / Michael Rothberg -- Holocaust and North Africa / Todd Presner